LABORATORY PROTOTYPE OF ELECTROCHEMICAL BIOSENSOR FOR THE QUANTITATIVE ANALYSIS OF ALANINE AMINOTRANSFERASE ACTIVITY - D.O. MRUGA; Y.R. VAKHOVSKY; S.V. DZYADEVYCH; O.O. SOLDATKIN (Biotechnologia Acta)
Aim. To develop an electrochemical biosensor for the quantitative assessment of alanine aminotransferase (ALT) activity.